Dysregulation of splicing proteins in head and neck squamous cell carcinoma. Issue 2 (1st February 2016) - Radhakrishnan, Aneesha; Nanjappa, Vishalakshi; Raja, Remya; Sathe, Gajanan; Chavan, Sandip; Nirujogi, Raja Sekhar; Patil, Arun H.; Solanki, Hitendra; Renuse, Santosh; Sahasrabuddhe, Nandini A.; Mathur, Premendu P.; Prasad, T. S. Keshava; et al.
ABSRTRACT: Signaling plays an important role in regulating all cellular pathways. Altered signaling is one of the hallmarks of cancers. Phosphoproteomics enables interrogation of kinase mediated signaling pathways in biological systems. In cancers, this approach can be utilized to identify aberrantly activated pathways that potentially drive proliferation and tumorigenesis. To identify signaling alterations in head and neck squamous cell carcinoma (HNSCC), we carried out proteomic and phosphoproteomic analysis of HNSCC cell lines using a combination of tandem mass tag (TMT) labeling approach and titanium dioxide-based enrichment. We identified 4, 920 phosphosites corresponding to 2, 212 proteins in six HNSCC cell lines compared to a normal oral cell line. Our data indicated significant enrichment of proteins associated with splicing. We observed hyperphosphorylation of SRSF protein kinase 2 (SRPK2) and its downstream substrates in HNSCC cell lines. SRPK2 is a splicing kinase, known to phosphorylate serine/arginine (SR) rich domain proteins and regulate splicing process in eukaryotes. Although genome-wide studies have reported the contribution of alternative splicing events of several genes in the progression of cancer, the involvement of splicing kinases in HNSCC is not known. In this study, we studied the role of SRPK2 in HNSCC. Inhibition of SRPK2 resulted in significant decrease in colony forming and invasive ability in a panel of HNSCC cell lines. Our results indicate that phosphorylation of SRPK2 plays a crucial role in the regulation of splicing process in HNSCC and that splicing kinases can be developed as a new class of therapeutic target in HNSCC.